Incorporation of privileged structures into 3-O-β-chacotriosyl ursolic acid can enhance inhibiting the entry of the H5N1 virus. Issue 18 (15th September 2019) - Li, Hui; Chen, Lizhu; Li, Sumei; Liao, Yixian; Wang, Lei; Liu, Zhihao; Liu, Shuwen; Song, Gaopeng
Graphical abstract: Abstract: The glycoprotein hemagglutinin of influenza virus plays a key role in the initial stage of virus infection, making it a potential target for novel influenza viruses entry inhibitors. Two "privileged fragments", 2-(piperidin-1-yl)ethan-1-amine and 2-(1, 3-oxazinan-3-yl)ethan-1-amine were integrated into 3- O -β-chacotriosyl ursolic acid producing new derivatives 5 and 6 with improved activity against IAVs in vitro . Mechanistically, compound 6 was effective in inhibiting infection of H1-, H3-, and H5-typed influenza A viruses by interfering with the viral hemagglutinin. Furthermore, the docking studies were in agreement with the antiviral data. These results showed that the title compound 6 as a new lead compound was meriting further optimization and development.